Little Evidence of a Role for the α1GABAA Subunit‐Containing Receptor in a Rhesus Monkey Model of Alcohol Drinking. (13th December 2013) - Sawyer, Eileen K.; Moran, Casey; Sirbu, Madelynn H.; Szafir, Melissa; Van, Michael; Namjoshi, Ojas; Phani Babu Tiruveedhula, VVN; Cook, James M.; Platt, Donna M.
<x xml:space="preserve">Abstract</x> Background Alcohol potentiates GABAergic neurotransmission via action at the GABAA receptor. α1 subunit‐containing GABAA receptors have been implicated as mediators, in part, of the behavioral and abuse‐related effects of alcohol in rodents. Methods We systematically investigated the effects of 1 α1‐preferring benzodiazepine agonist, zolpidem, and 2 antagonists, β‐carboline‐3‐carboxylate‐tert‐butyl ester (βCCT) and 3‐propoxy‐β‐carboline hydrochloride (3‐PBC), on oral self‐administration of alcohol (2% w/v) or sucrose solution and observable behavior in rhesus macaques. We compared these effects to those of the nonselective benzodiazepine agonist triazolam, antagonist flumazenil, and inverse agonist β‐carboline carboxylate (βCCE). Results Alcohol and sucrose solutions maintained reliable baseline drinking behavior across the study. The α1‐preferring compounds did not affect intake, number of sipper extensions, or blood alcohol levels (BALs) at any of the doses tested. Zolpidem, βCCT, and 3‐PBC increased latency to first sipper extension in animals self‐administering alcohol, but not sucrose, solution. Triazolam exerted biphasic effects on alcohol‐drinking behavior, increasing intake at low doses but decreasing BAL and increasing latency at higher doses. At doses higher than those effective in alcohol‐drinking animals, triazolam increased sucrose intake and latency. Flumazenil nonsystematically increased number of extensions for alcohol but decreased BAL, with no effects on sucrose drinking. βCCE decreased sipper extensions for alcohol and increased latency for first sucrose sipper extension, but full dose–effect relationships could not be determined due to seizures at higher doses. Conclusions Alcohol‐drinking animals appeared more sensitive to the effects of GABAergic compounds on drinking behavior. However, these results do not support a strong contribution of α1GABAA receptors to the reinforcing effects of alcohol in primates.